Financial Management Behavior: Implications Of Financial Literacy And Personality - et. al., Azib, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The fashion sector is one of the sectors worst affected by the pandemic. This study aims to determine and analyze the effect of financial literacy and personality on financial management behavior in creative economy actors in the fashion sub-sector in Bandung, Indonesia. Sampling in this study using purposive sampling technique where data is obtained through distributing questionnaires to 66 samples from 200 populations. Questionnaires and documents were used as data collection tools in this study. The analysis tool used is multiple linear regression with the help of the SPSS 26.0 program. The results of this study indicate that the variables of financial literacy and personality have a significant effect on financial management behavior partially and simultaneously. This means that in order to improve financial literacy and personality, it is necessary to study deeper and seek financial information.